FNAC of Normal Size Paediatric Lymph Nodes: Is it Justified? - Jain, Gaurav; Kalita, Deepti; Pant, Leela; Singh, Sompal (International Journal of Medical and Health Sciences Research, 2015)
This study was performed to assess utility of FNAC in normal size paediatric lymph nodes and to compare cytological findings in these normal size lymph nodes with enlarged lymph nodes. Two years retrospective study included all paediatric (age ≤ 14 years) patients referred to our department of cytopathology, for fine needle aspiration of lymph node swellings. Total 1524 lymph node FNAs were performed in 2011-12. Among these 484 (31.8%) were paediatric cases and were included in the study. Out of these cases 293 (60.5%) were normal by size and 191 (39.5%) were enlarged lymph nodes. It was observed that fine needle aspiration is more useful in large lymph node lesions than normal size lymph nodes for specific diagnosis. Still owing to small but finite possibility of finding specific lesions in normal sized lymph nodes, cytological examination of these cases is still recommended.